Brucellosis remains a neglected disease in District Muzaffargarh of Pakistani Punjab: A call for multidisciplinary collaboration - Sami Ullah; Tariq Jamil; Muhammad Asif; Waqas Ahmad; Heinrich Neubauer (German Journal of Veterinary Research)
Brucellosis is an important zoonotic infection of Pakistani ruminants. Muzaffargarh is an historically and agriculturally important district of Pakistan and the data on brucellosis remains scarce in this district. To overcome this gap, a preliminary study was performed to estimate the occurrence of brucellosis. A total of 53 sera were screened by Rose Bengal Plate Test (RBPT) and Serum Agglutination Test (SAT) followed by a Brucella genus specific conventional Polymerase Chain Reaction (PCR) and gel visualization of the PCR products. Four (7.54%) samples were positive by RBPT and SAT and only 1 (1.88%) sample was positive by PCR. The results point towards a persistent zoonotic threat in cattle in the district and the potential spill over infection when close contact to other animal species. Pasteurization of milk and regular screening of animals is recommended to prevent transmission.